2010
DOI: 10.5114/wo.2010.14132
|View full text |Cite
|
Sign up to set email alerts
|

Sporadic colorectal cancer – factors modulating individual susceptibility to cancer

Abstract: Rak jelita grubego (RJG) stanowi poważ-ny problemem epidemiologiczny w krajach wysoko rozwiniętych zarówno ze względu na stały wzrost zachorowań, jak i niewielki odsetek 5-letnich przeżyć pacjentów. Większość przypadków RJG (ok. 70%) stanowią zachorowania sporadyczne, których etiologia pozostaje niewyjaśniona. Ryzyko rozwoju sporadycznego RJG w dużej mierze zależy od indywidualnej wrażliwości na zachorowanie, kształtowanej przez współdzia-łanie czynników genetycznych z czynnikami środowiskowymi. Obecnie uważa … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 20 publications
0
12
0
Order By: Relevance
“…Also, various food products have an influence on neoplastic diseases development. Among Japanese inhabitants who consume the greatest quantities of rice a higher risk of colorectal cancer has been reported; a similar relation has been proved in Australia in case of high consumption of potatoes, while in American population, intake of higher number of snacks containing refined sugar correlated positively with a risk of cancer [26]. Among diet factors that may have an oncogenic effect, those that are perceived to be significant are high doses of nitrites and nitrates, salted foods, smoked and cured as well as too greasy or hot food [22][23][24].…”
Section: Discussionmentioning
confidence: 61%
See 3 more Smart Citations
“…Also, various food products have an influence on neoplastic diseases development. Among Japanese inhabitants who consume the greatest quantities of rice a higher risk of colorectal cancer has been reported; a similar relation has been proved in Australia in case of high consumption of potatoes, while in American population, intake of higher number of snacks containing refined sugar correlated positively with a risk of cancer [26]. Among diet factors that may have an oncogenic effect, those that are perceived to be significant are high doses of nitrites and nitrates, salted foods, smoked and cured as well as too greasy or hot food [22][23][24].…”
Section: Discussionmentioning
confidence: 61%
“…Diet rich in red and processed meat is a factor that increases a risk of colorectal cancer. Probably, it results from usage of nitrites and nitrates as meat preservatives, accumulation of heterocyclic amines and cyclic polycyclic hydrocarbons during thermal treatment of meat, as well as big amount of haem that stimulates production of n-nitroso-compunds in gastrointestinal tract, which may lead to cancer development [26]. Among other risk factors are vitamins deficiencies, especially vitamin A and iron that are favourable to development of oral cavity cancer.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The American Cancer Society estimates that among 1.5 million new cases of cancer diagnosed every year, at least 20% are the result of obesity. Epidemiological studies also show that obese patients treated oncologically have worse prognoses and greater mortality than patients with normal BMI [48,50]. The authors in their study have confirmed an increased risk of breast cancer in obese women compared to patients with normal weight.…”
Section: Biological Factorsmentioning
confidence: 88%